Effects of National policies and value chain in potato seed diversity in the municipality of Colomi (Cochabamba-Bolivia) - Escobar, A.G. (2014)
In the context of the project 'Improving the availability and the use of diverse seed and other planting materials to reduce vulnerability and improve food security for smallholders in vulnerable ecosystems', and in colaboration with the Fundación para la Promoción e Investigación de Productos Andinos (PROINPA) at the Municipality of Colomi-Department of Cochabamba, Bolivia, this master study identifies the main constrains of the potato seed system, as well as mapping, and understanding the key factors affecting farmer’s production, acquisition and distribution of potato seed in Bolivia.